2010
DOI: 10.1590/s0100-40422010000200024
|View full text |Cite
|
Sign up to set email alerts
|

Interferência da lignina na quantificação de radicais livres no processo de compostagem

Abstract: Recebido em 24/3/09; aceito em 5/8/09; publicado na web em 11/1/10 INTERFERENCE OF LIGNIN IN THE QUANTIFICATION OF FREE RADICALS IN THE PROCESS OF COMPOSTING.In this work was studied composts and their humic acids (HA) to evaluate the use of EPR in the monitoring of the humification. It was observed increase in the concentration of organic free radical (OFR) in all the composts, but in L1 the increase was more significant than L2 and L3. Research more detailed of L1 showed that the lignin is main source of OFR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 24 publications
0
4
0
3
Order By: Relevance
“…Although their origin is not fully understood, it has been suggested that these compounds are semiquinone or lignin-like free radicals, remnants of plant metabolism or produced by the oxidation of polyphenols or plant fatty acids ( 40 ). Studies suggest that the lignin is degraded by extracellular enzymes in smaller portions, which makes it susceptible to absorption by microbial cells, where it is then converted into phenols and quinones that are released with oxidative enzymes into the environment to be polymerized by the mechanisms of free radical formation ( 41 - 43 ). Alternatively, the process of pulping açaí and juçara in a depulper (or mixer) with water introduces excess air and may encourage the oxidation of fruit lipids.…”
Section: Resultsmentioning
confidence: 99%
“…Although their origin is not fully understood, it has been suggested that these compounds are semiquinone or lignin-like free radicals, remnants of plant metabolism or produced by the oxidation of polyphenols or plant fatty acids ( 40 ). Studies suggest that the lignin is degraded by extracellular enzymes in smaller portions, which makes it susceptible to absorption by microbial cells, where it is then converted into phenols and quinones that are released with oxidative enzymes into the environment to be polymerized by the mechanisms of free radical formation ( 41 - 43 ). Alternatively, the process of pulping açaí and juçara in a depulper (or mixer) with water introduces excess air and may encourage the oxidation of fruit lipids.…”
Section: Resultsmentioning
confidence: 99%
“…2018 of C-C bonds of aromatic rings, indicating the presence of lignins and N=C conjugated systems (Dobbss et al, 2009). Lignin is a compound of difficult decomposition, but it contributes to the formation of humic substances from its degradation and oxidation derivatives (Zhou et al, 2014;Fialho et al, 2010).…”
Section: Results and E Discussionmentioning
confidence: 99%
“…Temperature analyzes were performed daily, the analysis of pH, and moisture were carried out according to Fialho et al (2010). The elemental chemical analysis to determine the C/N ratio used a TruSpec CN Analyzer (LECO® brand, St. Joseph, Mi, USA).…”
Section: Temperature Moisture Ph and C/n Ratiomentioning
confidence: 99%